PENINGKATAN NILAI TAMBAH AGRIBISNIS MELALUI PENERAPAN INOVASI TEKNOLOGI USAHATANI PADI : STUDI KASUS KEGIATAN PRIMA TANI KABUPATEN MUSI RAWAS, SUMATERA SELATAN - Yanter Hutapea; Pandu AP Hutabarat; Tumarlan Thamrin (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2010)
Increasing of Agribusiness Value Added through Aplication of Rice Farming System TechnolgyInnovation: A Case Study of Prima Tani Activity In Musi Rawas District, South Sumatera. The application oftechnology innovation was conducted to overcome productivity disparity, to increase farmer income and to improvefarmer prosperity. Technology innovation on rice farming has been applied at “Prima Tani” activities on intensiveirrigation land since 2005 in South Sumatera Province. The aim of this study was to compare the application oftechnology innovation, cost production and rice farming income between participant and non participant farmers. Dataof rice farming activity during wet season in 2006/2007 was collected in Mei until September 2007 by interviewingparticipant farmer of Prima Tani in Kertosari Village and compared the result to the non participant in PurwakaryaVillage, Purwodadi Sub-district, Musi Rawas Regency. Samples was taken by Disproportionate Stratified RandomSampling. Result showed that the scores of technology application from participant and non participant farmerswere 6.38 and 4.37 respectively. However, there was no statistically difference between two farmers groups andincluded as medium category of technology application. The productivity of harvested dried rice of participantfarmers was 7. 8 kg/ha and 7.2 5 kg/ha for non participant farmers. Total cost of rice farming for participant andnon participant farmers were Rp.5,786,035/ha and Rp.6,663,875/ha respectively. Rice farming income of participantfarmer (Rp.8,228,9 5/ha) was significantly different from those in non-participant farmer (Rp.7,235,435/ha).Key words: Paddy, farming system, innovation, income. Penerapan teknologi inovasi dilakukan untuk mengatasi masalah senjang produktivitas, meningkatkanpendapatan usahatani dan kesejahteraan petani. Inovasi teknologi pada usahatani padi dilakukan melaluikegiatan Prima Tani lahan irigasi intensif Provinsi Sumatera Selatan sejak tahun 2005. Kegiatan ini bertujuanuntuk membandingkan penerapan teknologi usahatani padi, biaya yang dikeluarkan dan pendapatan usahatanipadi yang diperoleh oleh petani peserta dan bukan peserta Prima Tani. Pengumpulan data untuk meliput aktivitasusahatani dari musim hujan 2006/2007 dilakukan melalui wawancara pada bulan Mei-September 2007 padapetani peserta Prima Tani di Desa Kertosari dibandingkan dengan petani bukan peserta di Desa Purwakarya padakecamatan yang sama yaitu Kecamatan Purwodadi. Pengambilan sampel petani pemilik-penggarap secara AcakBerlapis Tak Berimbang. Hasil pengkajian menunjukkan bahwa skor penerapan teknologi pada petani pesertadan bukan peserta masing-masing 6,38 dan 4,37, tetapi secara statistik tidak berbeda nyata dan termasukdalam kategori penerapan teknologi pada tingkat sedang. Produksi gabah kering panen yang diperoleh petanipeserta dan bukan peserta sebanyak 7. 8 kg/ha dan 7.2 5 kg/ha. Biaya total yang dikeluarkan oleh petani pesertaPeningkatan Nilai Tambah Agribisnis melalui Penerapan Inovasi Teknologi Usahatani Padi :Studi Kasus Kegiatan Prima TaniKabupaten Musi Rawas, Sumatera Selatan (Yanter Hutapea, Pandu AP Hutabarat dan Tumarlan Thamrin)53sebesar Rp.5.786.035/ha, sedangkan petani bukan peserta sebesar Rp.6.663.875/ha. Pendapatan usahatani padiyang diperoleh petani peserta (Rp.8.228.9 5/ha) secara nyata dibanding petani bukan peserta (Rp.7.235.435/ha).Kata kunci: Padi,usahatani, inovasi, pendapatan.